TANGGUNG JAWAB PIDANA KORUPSI RUMAH SAKIT - Buamona, Hasrul (Al-Mazaahib: Jurnal Perbandingan Hukum, 2017)
Hospital is an institution that provides health services both preventive, promotive, curative and rehabilitation to the public at large. In addition, the hospital is a solid institution of capital, technology and human resources, thus potentially causing problems both internally and externally. Hospitals were previously regarded as social institutions that provide medical assistance to the wider community, but at the present time the position of hospitals has undergone a change, formerly in the form of social institutions becoming corporate institutions that lead to the dominant health services seeking economic benefits. Problems that arise in the present moment, when a medical error occurs by a doctor or health care provider, the patient only demands a criminal doctor and never asks for corporate criminal responsibility. With this issue that makes the author to interested in assessing whether the hospital can be held accountable corporate criminal. So in the study of the authors obtained a conclusion that the hospital can be asked for criminal responsibility because the hospital as a corporation is a legal subject that has rights and duties as well as humans. In addition the legal doctrine of Vicaroius Liability and Strict Liability clarifies that the employer / employer who hires a worker / employee can be responsible as long as his / her relationship with the relationship in a hospital / corporation.Kata Kunci : Tanggung Jawab Pidana, Korporasi, Rumah Sakit